Prognostic role of robinson cytological grading system in breast cancer in correlation with the histological grading of modified bloom richardson in Iraq - Kareem, Noora M.; Rahmatullah, Nihad Salih (International Journal of Research in Medical Sciences, 2018)
Background: The breast cancer is increasing in developing countries and the management options are widened, therefore providing the surgeon with accurate prognostic information on which the mode of therapy will be chosen became so important. Robinson grading system was found to be useful in grading breast carcinoma in fine needle aspirates. The objectives of the study were to estimate the benefits of using Robinson grading system in fine needle aspiration for breast cancer and to estimate the correlation of Robinson grading system in fine needle aspiration with histological grading. Methods: There were Seventy cases of invasive ductal carcinoma was graded on FNA aspirates by Robinson grading system using six cytological parameters (cell dissociation, cell size, cell uniformity, nucleolus, nuclear margin, and nuclear chromatin). Results: The concordance rate between grade I tumors on cytology and histology was 100%, while for grade II tumors it was 62.5% and for grade III tumors it was 100%. The absolute concordance rate was 87.5%, the Spearman rank correlation coefficient (r) was 0.762, p value was (0.00), the sensitivity of Robinson’s cytological grading system in cytological grade I tumors was 73.33% and specificity was 100%. In cytological grade II tumors the sensitivity was 100% and specificity was 76% and in cytological grade III tumors the sensitivity is 100% and specificity was 100%. Conclusions: Robinson’s cytological grading of breast carcinoma correlates well with Bloom-Richardson’s histological grading system and could be a helpful parameter in selecting a neoadjuvant treatment for the breast cancer patients on fine needle aspiration cytology alone.